Comparative Outcomes of Laparoscopic Gastrectomy and Open Gastrectomy for Scirrhous Gastric Cancer: A Multicenter Retrospective Cohort Study. Issue 2 (27th June 2021) - Fujita, Yusuke; Nishigori, Tatsuto; Kadokawa, Yoshio; Itami, Atsushi; Kondo, Masato; Hosogi, Hisahiro; Kanaya, Seiichiro; Kawada, Hironori; Hata, Hiroaki; Yamamoto, Michihiro; Kinjo, Yousuke; Tanaka, Eiji; et al.
Abstract : Recent efficacy and safety data suggest that laparoscopic gastrectomy (LG) is a viable alternative to open gastrectomy (OG). In this multicenter retrospective cohort study, we investigated the outcomes of LG versus OG for scirrhous gastric cancer. LG for scirrhous gastric cancer was not associated with worse survival than that for OG. Supplemental Digital Content is available in the text. Abstract : Objective: A multicenter retrospective cohort study was performed to compare the outcomes of laparoscopic gastrectomy (LG) versus open gastrectomy (OG) for scirrhous gastric cancer (GC) as a unique subtype also known as type 4 gastric cancer or linitis plastica. Background: Although data on the efficacy and safety of LG as an alternative to OG are emerging, the applicability of LG to scirrhous GC remains unclear. Methods: Patients with clinical type 4 GC undergoing gastrectomy at 13 hospitals from 2005 to 2015 were retrospectively reviewed. As the primary endpoint, we compared overall survival (OS) between the LG and OG groups. To adjust for confounding factors, we used multivariate Cox regression analysis for the main analyses and propensity-score matching for sensitivity analysis. Short-term outcomes and recurrence-free survival were also compared. Results: A total of 288 patients (LG, 62; OG, 226) were included in the main analysis. Postoperative complications occurred in 25.8% and 30.1%, respectively ( P = 0.44). No significant difference in recurrence-free survival was observed ( P = 0.72). The 5-year OS rates were 32.4% and 31.6% in the LG and OG groups, respectively ( P = 0.60). The hazard ratio (LG/OG) for OS was 0.98 (95% confidence interval [CI], 0.65–1.43) in the multivariate regression analysis. In the sensitivity analyses after propensity-score matching, the hazard ratio for OS was 0.92 (95% CI, 0.58–1.45). Conclusions: Considering the hazard ratios and 95% CIs for OS, LG for scirrhous GC was not associated with worse survival than that for OG.